INFLUENCE OF DISEASE ACTIVITY AND CHRONICITY ON BONE MINERAL DENSITY IN ANKYLOSING SPONDYLITIS - Şenay Özdolap; Selda Sarıkaya; Beyza Akdağ (Archives of Rheumatology, 2004)
In this study we aimed to examine the relationship between disease activity/duration and bone mineral density (BMD) on 37 patients with ankylosing sponylitis. Patients were classified according to disease activity and duration. We have used dual-energy x-ray absorptiometry (DEXA) to measure bone mineral density of lumbar spine, hip and forearm. A comparison of BMD between patients with active and inactive disease did not reveal a significant difference on all of the regions measured. Concerning disease duration, lumbar spine BMD was significantly reduced in early disease subject.